PO189 Autonomic failure caused by adult onset alexander disease with a novel gfap mutation. (1st December 2017) - Thompson, Andrew; Vichayanrat, Ekawat; Houlden, Henry; Iodice, Valeria; Ingle, Gordon
Abstract : Slowly progressive autonomic failure in adults presents a diagnostic challenge. Here we describe a patient with slowly progressive autonomic failure present for many years before any other clinically significant symptoms or signs appeared, who underwent detailed autonomic function testing, MR brain imaging and other neurological investigations on several occasions. After she developed bulbar dysfunction (causing two life-threatening choking episodes), pyramidal and sensory dysfunction, and characteristic brain imaging abnormalities were noted, a diagnosis of adult onset Alexander disease was made. GFAP sequencing demonstrated a heterozygous missense mutation (F199S) which has not been previously reported. Relatives affected by similar symptoms (orthostatic syncope and dysphagia) suggest autosomal dominant inheritance. On retrospective review, the imaging abnormalities were present from an early stage of her illness, when autonomic symptoms were present in isolation. We propose that a diagnosis of adult onset Alexander disease should be considered in cases of slowly progressive autonomic failure even in the absence of other clinical manifestations, and that awareness of the characteristic brain imaging abnormalities should allow early diagnosis which can be confirmed with genetic testing.